Group-centered prevention programs for at-risk students - Clanton Harpine, Elaine (Springer eBooks., 2011)
School psychologists, counselors, and educators in the K-12 setting face the daunting responsibility of finding balance between mandated testing, students? mental-health concerns, and additional academic help for at-risk students. One solution to this dilemma is to implement a school-based mental health approach that combines learning and counseling needs into a single program. Several types of successful programs are available, though week-long intensive programs have recently increased in popularity. Group-Centered Prevention Programs for At-Risk Students focuses on the development of such a week-long prevention program, and provides professionals with step-by-step directions to create their own program. It also focuses on the use of group-centered interventions as an opportunity to prevent at-risk behaviors as a means of correcting or changing dysfunctional behavior. This highly readable volume addresses such challenging issues as: Using self-reflection to teach writing skills. Increasing interpersonal interaction while honing etiquette. Enhancing group acceptance and reading comprehension. Rebuilding self-efficacy by increasing word recognition and decoding skills. With its solid research foundation combined with clear, practical program descriptions, this volume is an essential addition to the libraries of researchers and practitioners alike in the disciplines of school psychology, education, social work, psychotherapy and counseling, and clinical child psychology.